2022
DOI: 10.3748/wjg.v28.i16.1656
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA cancer susceptibility 20 regulates the metastasis of human gastric cancer cells via the miR-143-5p/MEMO1 molecular axis

Abstract: BACKGROUND Gastric cancer (GC) is considered as one of the most widespread malignancies. Emerging evidence has shown that lncRNAs can function as important oncogenes or tumor suppressors during GC progression. AIM To investigate the effect and mechanism of lncRNA cancer susceptibility 20 (CASC20) in the proliferation and metastasis of GC cells. METHODS Data mining and clinical samples were used to evaluate the expression of CASC20 in GC and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In this study, 11 lncRNAs with independent prognostic significance were screened using univariate Cox regression analysis, Lasso regression analysis, and multivariate Cox regression analysis to construct a prognostic model. Previous studies have shown that CASC20 is involved in the carcinogenesis of gastric cancer by competitively binding with Mir-143-5p and regulating the MEMO1 expression, thereby inducing epithelial-mesenchymal transition [15]. The SCAMP1 is a protein-coding gene.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 11 lncRNAs with independent prognostic significance were screened using univariate Cox regression analysis, Lasso regression analysis, and multivariate Cox regression analysis to construct a prognostic model. Previous studies have shown that CASC20 is involved in the carcinogenesis of gastric cancer by competitively binding with Mir-143-5p and regulating the MEMO1 expression, thereby inducing epithelial-mesenchymal transition [15]. The SCAMP1 is a protein-coding gene.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that LINC01711 might play a tumor-promoting role in HNSCC development. lncRNA cancer susceptibility 20 (CASC20) was reported to serve as a tumor promoter by promoting the metastasis of human gastric cancer cells by the miR-143-5p/MEMO1 molecular axis ( Shan et al, 2022 ). LINC01843 increased expression in patients and correlated with poor survival in lung adenocarcinoma ( Li et al, 2020 ; Zheng et al, 2021 ) and colon cancer ( Zhou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%